2012
DOI: 10.1056/nejmoa1204061
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk and Zoledronic Acid Therapy in Men with Osteoporosis

Abstract: Zoledronic acid treatment was associated with a significantly reduced risk of vertebral fracture among men with osteoporosis. (Funded by Novartis Pharma; ClinicalTrials.gov number, NCT00439647.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
240
2
14

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(258 citation statements)
references
References 29 publications
2
240
2
14
Order By: Relevance
“…For example, bisphosphonates and denosumab have been associated with osteonecrosis of the jaw and atypical femur fractures. In addition, bisphosphonates have been associated with atrial fibrillation and kidney damage (11,12). Therefore, the development of novel therapies for the treatment of osteoporosis is required.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bisphosphonates and denosumab have been associated with osteonecrosis of the jaw and atypical femur fractures. In addition, bisphosphonates have been associated with atrial fibrillation and kidney damage (11,12). Therefore, the development of novel therapies for the treatment of osteoporosis is required.…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparative study of once-yearly zoledronic acid 5 mg and once-weekly alendronate demonstrated noninferiority of zoledronic acid with regards to changes in BMD and bone turnover markers in men with osteoporosis (44). The most recently published multicentre double-blind, placebo-controlled trial of 1199 men reported fewer incident vertebral fractures with zoledronic acid (1.6% versus 4.9%, p=0.002), along with significant increases in BMD and decreases in bone turnover markers (45). Zoledronic acid use also has limitations and inconveniences: need for intravenous access and administration; monitoring of renal function, with dose adjustments and withholding to prevent renal injury in patients who develop renal impairment during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, in studies in which Brazilian researchers obtain regulatory approval before the end of recruitment, the country presents excellent performance, including a significant number of patients in record time, showing the high capacity of clinical research centers in Brazil. [17][18][19] It is estimated that these 18 studies alone represent a loss of financial investment of more than 14.6 million dollars. The financial losses are even more dramatic if we take into account other countries with similar geographical, cultural or economic features as the basis for potential studies that might have been allocated to Brazil: USD 32.5 million compared to the BRIC countries and USD 24.3 million compared to Latin America.…”
Section: Discussionmentioning
confidence: 99%